The Urgency of Indonesian Sustainable Palm Oil Certification for Oil Palm Plantation Companies in the State's Economic Growth - Jamaluddin; Faisal; Elidar Sari; Jumadiah (LPPM Universitas Malikussaleh, 2022)
The government is working on Indonesian Sustainable Palm Oil Plantations by issuing various regulations, both through the Presidential Regulation of the Republic of Indonesia Number 44 of 2020 concerning the Certification System for Indonesian Sustainable Palm Oil Plantations, as well as through the Regulation of the Minister of Agriculture Number 38 of 2020 concerning Implementation of Plantation Certification Indonesian Sustainable Palm Oil so that the oil palm plantation business obtains results that are economically feasible, socio-culturally feasible and environmentally friendly and increase the competitiveness of industrial palm oil products for the international market. The study method is normative juridical. In this study, an approach is used by identifying research objects and a statute approach. Based on the results of the study, the Government of Indonesia continues to make efforts for oil palm plantation companies to carry out ISPO certification. The government also issued various regulations to accelerate ISPO certification. It is suggested to the government continue to make efforts and be serious about accelerating ISPO certification by implementing various regulations that have been issued, including the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 18 of 2021 concerning the Facilitation of Development of Community Gardens in Surroundings, in addition to issuing the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 03 of the Year 2022 concerning Development of Human Resources, Research, and Development, Rejuvenation, as well as Facilities and Infrastructure for Oil Palm Plantations and several regions a Team for the Acceleration and Supervision of ISPO certification has been formed so that it has an impact on the country's economic growth.